Investment climate and employment growth: The impact of access to finance, corruption and regulations across firms - Reyes Aterido; Mary Hallward-Driemeier; Carmen Pagés (Inter-American Development Bank, Research Department, 2007)
Using firm level data on 70,000 enterprises in 107 countries, this paper finds important effects of access to finance, business regulations, corruption, and to a lesser extent, infrastructure bottlenecks in explaining patterns of job creation at the firm level. The paper focuses on how the impact of the investment climate varies across sizes of firms. The differences across size categories come from two sources. First, objective conditions of the business environment do vary systematically by firm types. Micro and small firms have less access to formal finance, pay more in bribes than do larger firms, and face greater interruptions in infrastructure services. Larger firms spend significantly more time dealing with officials and red tape. Second, even controlling for these differences in objective conditions, there is evidence of significant non-linearities in their impact on employment growth. The results suggest strong composition effects: A weak business environment shifts downward the size distribution of firms. In the case of finance and business regulations this occurs by reducing the employment growth of all firms, particularly micro and small firms. On the other hand, corruption and poor access to infrastructure reduce employment growth by affecting the growth of medium size and large firms. With significant differences between firms with less than 10 employees and SMEs, these results indicate significant reforms are needed to spur micro firms to grow into the ranks of the SMEs.
Keywords: 330; Unternehmensentwicklung; Beschäftigungseffekt; Betriebsgröße; Standortfaktor; Unternehmensfinanzierung; Regulierung; Korruption; Infrastruktur; Investitionsklima; Welt